The Informers - Patrick, Nigel 1913-1981; Whiting, Margaret 1924-2011; Finlay, Frank 1926-2016; Nesbitt, Derrin (Strawberry Media, 2012)
"The forerunner to the 1970's TV series "The Sweeney". Following a number of high profile robberies, Superintendant Bestwick decrees that his officers should adopt new scientific police methods and Chief Inspector Johnnoe is ordered to break contact with his network of snouts. However, when his best informant is murdered whilst on the trail of the gang responsible for a number of bank robberies, Johnnoe follows his detective instincts rather than orders. Following up Jim's earlier tip off, Johnnoe encounters two mobsters, Bertie Hoyle and his wily cohort Leon Sale. When Hoyle's attempt to bribe Johnnoe fails the cirminals fit him up with the help of Maisie, a cheap tart. Having been suspended, but released on bail, Johnnoe again ignores orders as he attempts to clear his name. With the help of the Ruskin family he tries to track down the murderers of his informer, solve the robberies and gain revenge on the criminals who framed him."
Original 1963
Bildformat 4:3, 1.33:1
Keywords: Police / Drama; Police; Drama; Film; DVD-Video